2003
DOI: 10.1038/sj.bjp.0705482
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor responses, and underlying mechanisms, to isoprostanes in human and porcine bronchial arterial smooth muscle

Abstract: 1 We investigated the effects of five different isoprostanes (8-iso PGE 1 , 8-iso PGE 2 , 8-iso PGF 1a , 8-iso PGF 2a and 8-iso PGF 2b ) on vasomotor tone in human and porcine bronchial arterial tissues. 2 In the human bronchial arteries, 8-iso PGE 2 and 8-iso PGF 2a evoked powerful constrictions (magnitudes several fold greater than the responses to high millimolar KCl) with negative log concentration causing 50% excitation (EC 50 ) values of 6.8 and 6.5, respectively; 8-iso PGE 1 was less potent (EC 50 not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 22 publications
5
23
0
Order By: Relevance
“…There is no obvious reason why the effects of 8-iso PGF 2a were apparently different to those of 8-iso PGE 2 , but it is evident that a different mechanism for 8-iso PGE 2 exists, which operates at least in part via the Rho kinase pathway. On speculation, this difference observed in relation to antagonism with Y-27632 can only be due to a relative difference in potencies observed in tissues, whereby 8-iso-PGE 2 is more potent (Oliveira et al 2000, Tazzeo et al 2003. There are no signalling pathways to our knowledge, known to operate via 8-iso-PGE 2 and 8-iso-PGF 2a directly.…”
Section: Discussionmentioning
confidence: 87%
“…There is no obvious reason why the effects of 8-iso PGF 2a were apparently different to those of 8-iso PGE 2 , but it is evident that a different mechanism for 8-iso PGE 2 exists, which operates at least in part via the Rho kinase pathway. On speculation, this difference observed in relation to antagonism with Y-27632 can only be due to a relative difference in potencies observed in tissues, whereby 8-iso-PGE 2 is more potent (Oliveira et al 2000, Tazzeo et al 2003. There are no signalling pathways to our knowledge, known to operate via 8-iso-PGE 2 and 8-iso-PGF 2a directly.…”
Section: Discussionmentioning
confidence: 87%
“…[99][100][101][102][103][104] Isoprostanes not only serve as biomarkers of the disease but also act as signal transduction molecules exerting multiple biological effects through prostanoid receptors and other signaling pathways. 47,[105][106][107] They can exert their effects on pulmonary vasculature in many ways, including pulmonary vasoconstriction, 48,108,109 induction of pulmonary endothelium to release endothelin 1, vasoconstriction in general, 49,110 and nonspecific effects on smooth muscle, such as hyperresponsiveness and hypertrophy, 50,51 thereby serving as important mediators in many lung pathologies including PAH.…”
Section: Role Of Lysophosphatidic Acidmentioning
confidence: 99%
“…Another point of interest is that some of the F-ring isoprostanes, such as 8-iso-PGF 2␣ and 8-iso-PGF 2␤ , produced, in our experiments, levels of contraction that are comparable with those induced by the E-ring isoprostanes. In contrast, in the porcine adult pulmonary vessels, F-ring isoprostanes induced markedly weaker contractions than E-ring isoprostanes (21,26). Finally, Janssen and Tazzeo (21) observed that, although the contractions induced in adult porcine PA and PV by 8-iso-PGE 1 , 8-iso-PGF 1␣ , 8-iso-PGF 2␣ , and 8-iso-PGF 2␤ were essentially completely prevented by TP receptor blockade, 8-iso-PGE 2 was able to evoke substantial contraction of PV in the maintained presence of TP receptor blockade.…”
Section: Discussionmentioning
confidence: 92%
“…However, when compared with U46619, 8-iso-PGF 2␣ was less potent by approximately one order of magnitude (20). Janssen and Tazzeo (21) and Tazzeo et al (26) examined the responses of adult porcine PA and veins to 8-iso-PGE 1 , 8-iso-PGE 2 , 8-iso-PGF 1␣ , 8-iso-PGF 2␣ , and 8-iso-PGF 2␤ , finding that 8-iso-PGE 2 was the most potent and efficacious in both PA and veins. However, isoprostanes exerted, in adult pulmonary vessels, maximal contractions that were 50 -90% of the response to 60 mM KCl, whereas the contractions that we describe in 12-to 24-h-old and 2-wk-old tissues were as much as 150 -200% of the response to KCl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation